2020
DOI: 10.3390/toxins12050311
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mycotoxin Detoxifiers on Health and Growth of Newly-Weaned Pigs under Chronic Dietary Challenge of Deoxynivalenol

Abstract: The efficacy of yeast-based mycotoxin detoxifiers on health and growth performance of newly-weaned pigs (27-d-old) fed diets naturally contaminated with deoxynivalenol was investigated. Sixty pigs were individually assigned to five treatments for 34 d: NC (negative control, 1.2 mg/kg of deoxynivalenol); PC (positive control, 3.2 mg/kg of deoxynivalenol); CYC (PC + clay/yeast culture-based product, 0.2%); CYE (PC + clay/yeast cell wall/plant extracts/antioxidants-based product, 0.2%); and CYB (PC + clay/inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 69 publications
(78 reference statements)
3
44
2
1
Order By: Relevance
“…In view of our results, even low levels of these mycotoxins, being below or close to No Observed Adverse Effect Level (NOAEL) values, should be considered as affecting the pig liver. The published data on the effects of such doses of DON and ZEN on the liver biochemistry are limited; however, they showed rather weak effects of these toxins on the serum activity of hepatic enzymes [ 58 , 59 , 60 ]. These findings agree with our morphological data showing that the responses of hepatocytes to intoxication with ZEN and DON seem to be adaptive.…”
Section: Resultsmentioning
confidence: 99%
“…In view of our results, even low levels of these mycotoxins, being below or close to No Observed Adverse Effect Level (NOAEL) values, should be considered as affecting the pig liver. The published data on the effects of such doses of DON and ZEN on the liver biochemistry are limited; however, they showed rather weak effects of these toxins on the serum activity of hepatic enzymes [ 58 , 59 , 60 ]. These findings agree with our morphological data showing that the responses of hepatocytes to intoxication with ZEN and DON seem to be adaptive.…”
Section: Resultsmentioning
confidence: 99%
“…Immuno-stimulation induced by AFB1 increases the synthesis of inflammatory markers and free radicals, which lead to chronic inflammation and cancer [ 42 , 43 ]. Anti-inflammatory activities of plant bioactive compounds have been reported in acute and chronic inflammation in animal models [ 44 , 45 ], and recent data have shown that they can be used for counteracting the toxic effect of AFB1 [ 24 , 46 , 47 ]. Our previous results have shown that GSM addition into AFB1-contaminated diet induced the amelioration of liver injuries and decreased inflammation and oxidative stress in the liver of intoxicated piglets by decreasing the MAPKs and NF-κB signaling pathways overexpressed by the AFB1 diet [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Body weight of pigs and feed consumption by pigs were recorded weekly and used to obtain average daily gain (ADG), average daily feed intake (ADFI), and gain to feed ratio (G/F). On d 35, 10 mL blood samples from the external jugular vein were collected with 0.8 × 32 mm needles (Eclipse, Becton Dickinson Vacutainer Systems, Franklin Lakes, NJ, USA) and serum blood collection tubes (Becton Dickinson Vacutainer Systems, Franklin Lakes, NJ, USA) using a vacutainer tube holder, following procedures routinely employed by our research group [ 20 , 86 , 87 ]. Serum samples were stored at −80 °C in a freezer (812660-760, Thermo Fisher Scientific, Waltham, MA, USA) in 1.5 mL tubes (Fisherbrand, Fisher Scientific, Hampton, NH, USA) after centrifugation at 1509× g at 4 °C for 15 min (5811F, Eppendorf, Hamburg, HH, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Ten pictures of each pig were used to measure gut morphology by a single researcher choosing a well-oriented villus and its associated crypt. Measurements included: villus width (at half of villus height), villus height (from tip of the villus to top of the crypt), crypt depth (from top to bottom of the crypt), and calculating villus height: crypt depth [ 86 ]. The proportion of proliferating cells in the crypt was also estimated by calculating the proportion of cells positive to Ki-67 after taking pictures at 40× in Sony Van–Ox S microscope (Opelco, Washington, DC, USA) and processing in ImageJS tool [ 92 ] for analysis as described by Holanda and Kim [ 86 ].…”
Section: Methodsmentioning
confidence: 99%